MLST reveals a separate and novel clonal group for Acidovorax avenae strains causing red stripe in sugarcane from Argentina - Fontana, Paola Daniela (2018)
Acidovorax species cause a wide range of economically important diseases in monocotyledonous and dicotyledonous plants, including sugarcane, corn, rice, oats, millet, foxtail watermelon and orchids. In Argentina, the red stripe disease of sugarcane caused by A. avenae affects 30% of the milling stems with important economic losses. To explore the genetic diversity of this bacterium associated with red stripe in Argentina, MLST was applied. This study included 15 local strains isolated from four different sugarcane planting regions and selected after RAPD analysis and reference strains of A. citrulli, A. avenae, and A. oryzae to investigate their phylogenetic relationships. MLST analysis resulted in five sequence types (STs) among the sugarcane A. avenae strains which constitute a clonal complex, meaning a common and close origin. Sugarcane strains were related to A. avenae from other hosts and distant to A. citrulli. Signals of frequent recombination in several lineages of A. avenae was detected and we observed that A. oryzae is closely related to A. avenae strains. This study provides valuable data in the field of epidemiological and evolutionary investigations of novel clone of A. avenae strains causing sugarcane red stripe. The knowledge of the genetic diversity and the specificity strain-host are important to select the genotypes with the best response to the red stripe disease.